PENGEMBANGAN KAPASITAS : STRATEGI INTERNASIONALISASI PENDIDIKAN TINGGI DI INDONESIA - Retno Sunu Astuti (Departemen Administrasi Publik, Universitas Diponegoro, 2016)
Higher education is one of the key factors in the effort to improve the lives and well-being of a nation. The experience of developed countries in Asia showed that the quality of higher education correlated significantly with the increased competence of human resources as a whole which eventually forms a high competence in the global competition. Globalization proactively answered by the governments in various parts of the world through international cooperation in the form of teaching, research, and dedication to the university in the form of the internationalization program. Through descriptive qualitative method enriched by quantitative techniques with intrinsic case study design (intrinsic case study), this research found that the success of internationalization is driven by capacity building supported by horizontal and hands on leadership. Therefore, the leadership of a university is not only an academic but it must be a manager who is able to read the signs of change.